CompTIA A+ Core 2 (220-1002) : complete video course - Prowse, David L. (LiveLessons (Indianapolis, Ind.), 2020)
CompTIA A+ Core 2 (220-1002) Complete Video Course is a unique video product that provides a solid understanding of A+ skills. The purpose of these videos is to act as quick, concise, hands-on training that is easily absorbed. In this best-selling author and instructor-led course you will get coverage of every objective and topic in the CompTIA A+ Core 2 (220-1002) exam. It is also full of hands-on demos so you can see real hardware and software presentations. David Prowse walks you through the details you need to not only pass the test but troubleshoot and fix real hardware, software, and network problems for your career. The author also includes tech tips throughout to give you insider info on troubleshooting, repair, and maintenance. This title can be used as your sole resource for learning the material needed to study for and pass the test. You can also use this as a supplement to other A+ training. There are a total of four domains that map to the main objectives of the CompTIA A+ Core 2 (220-1002) exam. These domains contain 33 lessons with video totaling more than 26 hours of hands-on demonstrations, audio instruction, animations, whiteboard training, and video screencasting. He includes hands-on configuration labs; laptop, smartphone, and device hardware labs; and live-action troubleshooting labs.